: Gestión pedagógica en el aula: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica en los Centros Educativos: Escuala de Práctica Docente Portoviejo de la Ciudad de Cariamanga y la Escuela Dra. Guadalupe Larriva G. del barrio la Fragua, parroquia el Ingenio, Cantón Espíndola de la Provincia de Loja, en el año lectivo 2011-2012 - Moreno Gaona, Lisvia Janneth (2013)
This study SCHOOL SOCIAL CLIMATE FROM THE COLLECTION OF STUDENTS AND TEACHERS OF BASIC EDUCATION. Induces known learning management and social climate of the classroom. , Under this premise , clear, precise and achievable research was performed , with improvement alternatives , with the intention of rescuing an atmosphere of trust and mutual collaboration to overcome obstacles of daily living within the classroom , the research was conducted in the " Portoviejo " Cariamanga school and School " Dr. Guadalupe Larriva " El Ingenio, Canton Espíndola, during the academic year 2011-2012 , the survey and interviews with teachers and students was applied , using descriptive , analytic, synthetic , inductive, deductive , statistical, hermeneutical methods, techniques, reading maps conceptual , graphic organizers , observation and survey. Most parents have primary education, many students live only mom who reviews the work extraclase pursuant to shortcomings observed teachers should encourage cooperative learning that leads to improved academic performance by offering quality education. At the discretion of readers this research hoping for a bibliographic reference tool and source for future research.